Research of inequality in education in contemporary Russian sociology - Yu B Epikhina (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2009)
The axis of the publication is the survey of the major approaches applied to the analysis of the issues pertaining to inequality in educational opportunities in contemporary Russian sociology. The author highlights three lines of research of inequality in the given sphere and provides a detailed description of each of them.